773 CONTRAST-ENHANCED EXCIMER LASER CORONARY ANGIOPLASTY IN THE TREATMENT OF HEAVILY CALCIFIED LESIONS: A STEPWISE APPROACH. (15th December 2022) - Caminiti, Rodolfo; Vetta, Giampaolo; Parlavecchio, Antonio; Mazzone, Paolo; Giacchi, Giuseppe; Sacchetta, Giorgio; Della Rocca, Domenico Giovanni; Magnocavallo, Michele; Virga, Vittorio; Costa, Francesco; Di Bella, Gianluca; Carerj, Scipione; et al.
Abstract: Introduction: The treatment of heavily calcified lesions is a challenge for the interventional cardiologist. The Excimer laser coronary atherectomy (ELCA) is a plaque modification tool and the main mechanism of action seems to be the photomechanical delivering acoustic pressure with a mechanical disruption of the plaque in front of the catheter tip. Objective: To evaluate the effectiveness of the contrast-enhanced ELCA by a stepwise approach, with incremental frequency/fluency in the treatment of calcified lesions in different contexts. Methods: We retrospectively enrolled consecutively all patients undergoing contrast-enhanced ELCA-assisted PCIs between 2018 and 2021 at the Cardiology Unit of "Umberto I" Hospital of Syracuse (Italy). The frequency/fluency ELCA profile used with a stepwise approach were 50/50, 60/60, 70/70 and 80/80. ELCA technical success was defined as the laser catheter crossing the entire length of the target lesion established by angiographic evidence of the catheter tip in the artery distal to the stenosis. Procedural success was defined as <30% residual stenosis after laser and adjunctive therapy. Clinical success requested procedural success with absence of major adverse cardiac events at hospital discharge. Major adverse cardiac events included death of all causes, myocardial infarction, need for target lesion revascularization, tamponade, and life-threatening arrhythmias. Results: We enrolled 114 patients who underwent contrast-enhanced ELCA-assisted PCI. 58% of the patients had acute coronary syndrome and 42% had chronic coronary syndrome. The left anterior descending artery was the target vessel in 42.1% of cases, the right coronary artery in 26.3%, the circumflex in 10.5%, and the left main artery in 2.3%. The main indication for ELCA was intrastent restenosis (56.2%). The median stenosis was 90% (80% – 90%). The ELCA catheter tip was 0.9 mm and 1.4 mm was employed in the 89.5% and 10.5% of cases respectively. The most used frequency/fluency profile was 70/70 (39.5%) followed by 60/60 (31.6%), 50/50 (15.8%) and 80/80 (13.2%). Use of contrast-enhanced ELCA was associated with high technical success rate (97.4%), procedural success rate (93.7%), and clinical success rate (97.1%). Conclusions: In Conclusion, the contrast-enhanced ELCA seems to be a safe and effective treatment for management of calcified lesions.